Proteomic Analyses of Chlorhexidine Tolerance Mechanisms in Delftia acidovorans Biofilms - Tara Rema (American Society for Microbiology, 2016)
ABSTRACT Protein expression and fatty acid profiles of biofilm cells of chlorhexidine-tolerant Delftia acidovorans (MIC = 15 µg/ml) and its chlorhexidine-susceptible mutant (MIC = 1 µg/ml) were investigated. The chlorhexidine-susceptible mutant (MT51) was derived from the parental strain (WT15) using Tn5 transposon mutagenesis. The disrupted gene was identified as tolQ, a component of the tolQRAB gene cluster known to be involved in outer membrane stability. Proteomic responses of biofilm cells were compared by differential in-gel electrophoresis following exposure to chlorhexidine at sub-MIC (10 µg/ml) and above-MIC (30 µg/ml) concentrations. Numerous changes in protein abundance were observed in biofilm cells following chlorhexidine exposure, suggesting that molecular changes occurred during adaptation to chlorhexidine. Forty proteins showing significant differences (≥1.5-fold; P < 0.05) were identified by mass spectrometry and were associated with various functions, including amino acid and lipid biosynthesis, protein translation, energy metabolism, and stress-related functions (e.g., GroEL, aspartyl/glutamyl-tRNA amidotransferase, elongation factor Tu, Clp protease, and hydroxymyristoyl-ACP dehydratase). Several proteins involved in fatty acid synthesis were affected by chlorhexidine, in agreement with fatty acid analysis, wherein chlorhexidine-induced shifts in the fatty acid profile were observed in the chlorhexidine-tolerant cells, primarily the cyclic fatty acids. Transmission electron microscopy revealed more prominent changes in the cell envelope of chlorhexidine-susceptible MT51 cells. This study suggests that multiple mechanisms involving both the cell envelope (and likely TolQ) and panmetabolic regulation play roles in chlorhexidine tolerance in D. acidovorans. IMPORTANCE Delftia acidovorans has been associated with a number of serious infections, including bacteremia, empyema, bacterial endocarditis, and ocular and urinary tract infections. It has also been linked with a variety of surface-associated nosocomial infections. Biofilm-forming antimicrobial-resistant D. acidovorans strains have also been isolated, including ones displaying resistance to the common broad-spectrum agent chlorhexidine. The mechanisms of chlorhexidine resistance in D. acidovorans are not known; hence, a chlorhexidine-susceptible mutant of the tolerant wild-type strain was obtained using transposon mutagenesis, and the proteome and ultrastructural changes of both strains were compared under chlorhexidine challenge.